Pandemic Health Science Communications: Lessons Learned (or Not Learned). Issue 2 (March 2022) - Rowe, Sylvia; Alexander, Nick
Abstract : When the authors, in an article 2 years ago, explored early communication lessons from COVID-19, it was thought that the world would likely have gotten past the pandemic by publication date. Now, nearly 2 years later, the virus continues to wreak public fear and seemingly confound policy makers, the health/medical community, and risk communicators about how to address the virus. It is time to take stock again of what has worked and what has made matters worse in communicating about severe acute respiratory syndrome coronavirus 2—in other words, what may have gone wrong and what seems to have gone right. In the present article, the authors review existing risk communication guidelines and offer suggestions for additions/revisions in light of the world's COVID-19 experience. Specifically, they discuss how communicators might mitigate the politicization of pandemic messages, the need for balancing effective messaging, potential harms to public well-being, risk/benefit analysis, and the necessity of what the National Academies of Sciences, Engineering, and Medicine has called "radical transparency."